8x-24=8x+3(8+2x)

Simple and best practice solution for 8x-24=8x+3(8+2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-24=8x+3(8+2x) equation:


Simplifying
8x + -24 = 8x + 3(8 + 2x)

Reorder the terms:
-24 + 8x = 8x + 3(8 + 2x)
-24 + 8x = 8x + (8 * 3 + 2x * 3)
-24 + 8x = 8x + (24 + 6x)

Reorder the terms:
-24 + 8x = 24 + 8x + 6x

Combine like terms: 8x + 6x = 14x
-24 + 8x = 24 + 14x

Solving
-24 + 8x = 24 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
-24 + 8x + -14x = 24 + 14x + -14x

Combine like terms: 8x + -14x = -6x
-24 + -6x = 24 + 14x + -14x

Combine like terms: 14x + -14x = 0
-24 + -6x = 24 + 0
-24 + -6x = 24

Add '24' to each side of the equation.
-24 + 24 + -6x = 24 + 24

Combine like terms: -24 + 24 = 0
0 + -6x = 24 + 24
-6x = 24 + 24

Combine like terms: 24 + 24 = 48
-6x = 48

Divide each side by '-6'.
x = -8

Simplifying
x = -8

See similar equations:

| 7-2exp(x)=0 | | 8x-12=-2(-4x+4) | | 73=-7x-3(-4x-16) | | e=6p-1x-2 | | .10+.25(n+5)=4.40 | | logx=3.6 | | 73=-7x-39(-4x-16) | | 75-10-8+12-18=x | | 5x+1/8=0.5 | | 5(x-6)=7x-6 | | exp(x)-2=4 | | 17+8=-3c-25 | | 36=5(3c-12)+4(2c+1) | | exp(7x)=8 | | 75-10-8+12=x | | 8x+4y=72 | | .10n+.25(n+6)=4.65 | | 4x+8y=72 | | F(x)=(7-2x)(x+5) | | (x^2)+x-30= | | -34+4v=6(7v+7) | | -2000000+-80000x=-3600000 | | 32-8b=-(1+2b) | | y=10x+13 | | x-23+x+89=180 | | c+t+5=415 | | -2000000+80000x=3600000 | | 96=10x-14 | | -5r-35=-6(r+6) | | 87=15x+13 | | -2(8-8x)+3=14+7x | | 2q-13=3 |

Equations solver categories